PENGARUH AUDIT TENURE, AUDIT DELAY, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX 70 (JII70) TAHUN 2022-2024 - Nurjanah, Nurjanah; Youdhi Prayogo; Faturahman, Faturahman (Nusantara Hasana Journal, 2026)
The purpose of this research is to examine the sharia audit quality of firms listed on the Jakarta Islamic Index 70 (JII70) from 2022 to 2024 and how audit tenure, audit delay, and audit rotation impacted it. In order to maintain stakeholders' and investors' faith in Islamic enterprises' financial statements, Sharia audit quality is crucial. The quantitative methodology used in this study is based on secondary data collected from yearly financial statements and reports prepared by independent auditors. All firms listed on the JII70 make up the study population. Over the course of three years, 15 organizations were selected as research samples by purposive selection. With the help of statistical software, panel data regression is used as the data analysis approach. According to the findings, sharia audit quality is positively impacted by audit rotation and audit tenure, and negatively impacted by audit delays. The quality of sharia audits is significantly impacted by audit tenure, audit delay, and audit rotation all at once. These findings suggest that appropriate audit tenure, audit delay management, and audit rotation are important factors in maintaining auditor independence and enhancing sharia audit quality. This study is expected to contribute theoretically to the development of sharia auditing literature and provide practical considerations for auditors, corporate management, and Islamic capital market regulators.